Effectiveness of an avatar educational application for improving heart failure patients' knowledge and self‐care behaviors: A pragmatic randomized controlled trial. (27th July 2020) - Wonggom, Parichat; Nolan, Paul; Clark, Robyn A.; Barry, Tracey; Burdeniuk, Christine; Nesbitt, Katie; O'Toole, Kathryn; Du, Huiyun
Abstract: Aim: To evaluate the effectiveness of education using avatars for improving patients' heart failure knowledge and self‐care. Background: A lack of knowledge and self‐care contributes to poor outcomes and rehospitalization for people with heart failure. Design: A multi‐centred, non‐blinded pragmatic randomized controlled trial. Methods: Heart failure patients were randomly assigned to intervention (avatar education application) or usual care groups. Participants were followed up at baseline, 30 and 90 days. ANCOVA was used to compare the scores of heart failure knowledge and self‐care, between the two groups. Fisher's exact test was used to compare the two groups' heart failure‐cause readmission. Bivariate exact binary logistic regression was used to identify the predictors associated with baseline levels of knowledge. Results: A total of 36 participants were recruited (between October 2018 ‐ March 2019). The mean age of participants was 67.5 ( SD 11.3) years. At enrolment, approximately half (47.2%) have been living with Heart Failure for over 5 years. Two groups were comparable at baseline in their demographic and clinical characteristics. At 90 days, the intervention group participants had a higher increase in knowledge score on the Dutch Heart Failure Knowledge Scales compared with the control group (22.2% versus 3.7%  P  = .002, partial  η 2  = 0.262, 95% CI −2.755 to −0.686). There was no between‐group difference observed at 30‐ or 90‐day follow‐up, on self‐care behaviour (Self‐care of heart failure index) or healthcare use. Overall satisfaction with the avatar app was 91.3%. Conclusion: The addition of a co‐designed avatar app to usual care improved knowledge in our group of Heart Failure participants at 30 days and continued to increase up to 90 days. The results suggest that our avatar app was perceived as an enjoyable and engaging means of delivering critical knowledge and self‐care information. Impact: Heart failure is associated with poor clinical outcomes (i.e., readmission rates and mortality rate) and substantial economic burden. The effectiveness of Heart Failure patient education using avatar have not been investigated previously.  In this study, the avatar app improved knowledge and self‐care behaviours. This innovation could be used at the bedside, at home by nurses, patients and families. Trial Registration: Australian New Zealand Trial Registry ACTRN12617001403325. Abstract : 目的: 探讨avatars教育对提高心衰患者心衰知识和自我保健能力的有效性。 背景: 缺乏知识和自我护理能力可导致心力衰竭患者病情恶化和再次入院。 设计: 多中心、非盲态且实用的随机对照试验。 方法: 心力衰竭患者被随机分配到干预组(avatar教育应用程序)或普通护理组。应分别在基线水平, 治疗后30天和90天对参与者进行随访。利用协方差分析法对此两组患者的心衰知识和自我保健得分进行评估。利用费希尔精确检验方法对两组心力衰竭患者的再入院率进行比较。此外, 采用二元精确及二元逻辑回归分析法确定与基线知识水平相关的预测因子。 结果: 目前, 共招募36名参与者(2018年10月至2019年3月)。参与者的平均年龄为67.5岁(标准偏差为11.3岁)。近半数(47.2%)的患者有至少5年的心力衰竭患病史。上述两组在人口统计学和临床特征方面具有可比性。治疗后90天, 干预组内参与者在荷兰心力衰竭知识量表上的知识得分较对照组的增长更高(22.2%比3.7% P =.002, 部分 η 2 = 0.262, 95%CI−2.755−0.686)。根据治疗后30天或90天的随访结果, 上述两组患者在自理行为(心衰自理指数)或医疗保健方面无组间差异。患者对avatar应用程序的总体满意度为91.3%。 结论: 在日常护理过程中, 使用经共同设计的avatar应用程序, 以实现在30天内提高此组心力衰竭患者的知识水平, 并在90天内持续增加。结果表明, 此avatar应用程序可满足患者需求, 极具吸引力, 且可用于传递关键知识和自我保健信息。 影响: 心力衰竭与不良临床结果(即再入院率和死亡率)和沉重经济负担相关。此前, 并无有关Avatar应用对心力衰竭患者教育的有效性研究。这一创新可由护士、患者及其家人在床边或家中应用。临床试验注册:澳大利亚‐新西兰试验注册处, 注册号:ACTRN12617001403325。